2011
DOI: 10.1016/j.foodchem.2010.12.063
|View full text |Cite
|
Sign up to set email alerts
|

Immunomodulatory effect of mushrooms on cytotoxic activity and cytokine production of intestinal lamina propria leukocytes does not necessarily depend on β-glucan contents

Abstract: We evaluated the effects of seven mushroom extracts (Grifola frondosa, Pholiota nameko, Panellus serotinus, Hypsizygus marmoreus, Pleurotus cornucopiae, Armillaria mellea, and Flammulina velutipes) on cytotoxic activity and cytokine production of lamina propria leukocytes (LPLs) isolated from rat small (S) and large (L) intestinal mucosa. Boiling water extracts from seven species of mushrooms showed no direct cytotoxicity against the YAC-1 target cells. However, prominent increases of cytotoxicity were observe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0
2

Year Published

2012
2012
2020
2020

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 19 publications
(9 citation statements)
references
References 38 publications
(31 reference statements)
0
6
0
2
Order By: Relevance
“…The currently available chemical drugs used as immunomodulators have shown to possess a higher risk profile when compared to natural immunomodulators (El Enshasy and Hatti-Kaul, 2013; Shukla et al, 2014). Mushrooms have been known for their medicinal value for decades, and many of the compounds extracted from mushrooms have been demonstrated to have modulatory effects on the immune system (Lee et al, 2011). F. velutipes is one of the medicinal mushrooms that exhibits immunomodulatory activities.…”
Section: Biological Activities Of F Velutipesmentioning
confidence: 99%
See 1 more Smart Citation
“…The currently available chemical drugs used as immunomodulators have shown to possess a higher risk profile when compared to natural immunomodulators (El Enshasy and Hatti-Kaul, 2013; Shukla et al, 2014). Mushrooms have been known for their medicinal value for decades, and many of the compounds extracted from mushrooms have been demonstrated to have modulatory effects on the immune system (Lee et al, 2011). F. velutipes is one of the medicinal mushrooms that exhibits immunomodulatory activities.…”
Section: Biological Activities Of F Velutipesmentioning
confidence: 99%
“…Similarly, the water extract of F. velutipes was also demonstrated to enhance splenocyte proliferation and Th1 cytokine production in mice (Ryu et al, 2014). Another interesting study by Lee et al (2011) showed that the boiling water mushroom F. velutipes extract potentiated the production of IFNγ and cytotoxic activity against YAC-1 (lymphoma cell) of large intestinal lamina propria leukocytes but not small intestinal lamina propria leukocytes (Lee et al, 2011). …”
Section: Biological Activities Of F Velutipesmentioning
confidence: 99%
“…However, there were few studies on its other chemical constituents, especially the water‐soluble components, which also have several bio‐activities, such as anti‐oxidant activity (Huang and Zhang ). It has been reported that the immuno‐modulatory effect of boiling water extracts from several mushrooms on cytotoxic activity was not necessarily related to their β‐glucan content (Lee and others ). This suggests that sometimes polysaccharides may not be the main active component, and other components in Tricholoma matsutake may also be responsible for the activity of the extracts.…”
Section: Introductionmentioning
confidence: 99%
“…This study found the potential ability of G. applanatum mushroom extract to activate immunologic parameters in rainbow trout. Lee et al [45] found that the mushroom could increase the concentration of IFNγ that has a toxic function against lymphoma cell. The polysaccharides of needle mushroom were found to produce different cytokines and increase the weight of immune stimulating organs in laboratory animals [4,5].…”
Section: Immune Functionsmentioning
confidence: 99%